Delayed care-seeking and its underlying factors among patients with tuberculosis in Yangon, Myanmar - May Chan Oo; Kyaw Zarni Tun; Kyaw Ko Ko; Pyae Linn Aung (Journal of Infection in Developing Countries)
Introduction: Tuberculosis (TB) remains a major public health problem in Myanmar. Early care-seeking behaviors play a significant role in reducing TB transmission and speeding recovery. This study was conducted to estimate the proportion of patients with TB who delayed care-seeking and to identify underlying factors.